Learning Strategy Toward Attitudes And Motivational Orientations OF Indonesian Learners In Learning English As A Foreign Language - Rizka Maulina Wulandari; Jannatul Laily Noviabahari; Muhammad Isa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
In Indonesia, where different languages co-exist and where English is used as a foreign language, the learners' attitudes and motivational orientation toward English play an important role in formulating effective learning strategies. This article aimed to examine the attitudes of Indonesian students toward learning English as a foreign language and to understand the motivational orientations that result from their attitudes. A secondary objective of this research was to find the appropriate learning strategy that can be used for high school students in Indonesian education based on the result of the research. Fifty high school students in the second grade from sciences and social sciences major were asked to respond to questionnaires that measured their attitudes and orientations. The results indicated positive attitudes toward learning English as a foreign language with a clear instrumental orientation. Hence, the study highlighted that Self-Regulated Learning (SRL) became the appropriate learning strategy. Despite a strong desire to learn English to gain access to international markets, the status of Bahasa remains secure as it is viewed as a symbol of national integration.